Khotbah Kristosentris: Implikasi Kisah Para Rasul 2:14-40 bagi Pengkhotbah Masa Kini - Mudak, Sherly; Manafe, Ferdinan S.; Butar-Butar, Gloria C.E.; Talan, Yerni Maryuna (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
Preaching has a central role in the life of the church as a means of conveying the truth of God's word, building faith, and inspiring the congregation's life in accordance with God's will. However, the times have shown a shift in the focus of preaching from Christocentricity to pragmatic themes orientated towards human needs, which can reduce its theological relevance. This study aims to analyse Peter's sermon in Acts 2:14-40 as a model of Christocentric preaching and explore its implications for preachers today. The method used is a literature study with a thematic approach to explore the main elements in Christocentric preaching, such as the proclamation of Christ, His resurrection, and the call to repentance. The results show that Peter's sermon provides a strong example of the integration of Old Testament prophecy with New Testament fulfilment, the focus on Christ's resurrection, and its impact in bringing repentance and transformation of the congregation's lives. The research also confirms that Christocentric preaching is relevant today as a means of building faith, providing eschatological hope, and encouraging the mission of the church.